Augmentation the width of a keratinized attached gingiva in patients with dental implantation - T. V. Brailovskaya; A. P. Vedyaeva; R. V. Kalinin; E. A. Garibyan; Z. A. Tangieva; A. M. Deniev (Сеченовский вестник)
To date, there has been an increase in the scientiﬁc interest in the state of soft tissues surrounding dental implants and their inﬂuence on the long-term prognosis of implant treatment. It is known, that the risk factors for the development of periimplantitis include a deﬁciency or complete absence of an attached keratinized gingiva in the area of implants. The article provides a comparative analysis of various methods of mucogingival surgery in the ﬁeld of dental implants using free gingival autografts and xenogenic dermal matrices.